2015
DOI: 10.1002/ptr.5348
|View full text |Cite
|
Sign up to set email alerts
|

A Review: The Pharmacology of Isoliquiritigenin

Abstract: Isoliquiritigenin (ISL) is one of the bioactive ingredients isolated from the roots of plants belonging to licorice, including Glycyrrhiza uralensis, Mongolian glycyrrhiza, Glycyrrhiza glabra, and so forth. Liquiritigenin is available in common foods and alternative medicine, and its derivative-ISL is applied into food additives and disease treatment like cancer therapy, antibiotic therapy, and so on. This review aims at providing a comprehensive summary of the pharmacological activities of ISL. The informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(150 citation statements)
references
References 82 publications
1
146
0
3
Order By: Relevance
“…Notably, the roots of licorice (Glycyrrhiza) have been used to treat inflammation, gastric ulcers and atherosclerosis, in folk and traditional herbal medicine in Eastern Asian countries, including Korea, Japan and China (30,31). Licorice root contains alkaloids, polysaccharides, and flavonoids (32).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the roots of licorice (Glycyrrhiza) have been used to treat inflammation, gastric ulcers and atherosclerosis, in folk and traditional herbal medicine in Eastern Asian countries, including Korea, Japan and China (30,31). Licorice root contains alkaloids, polysaccharides, and flavonoids (32).…”
Section: Discussionmentioning
confidence: 99%
“…Isoliquiritigenin, one of the bioactive components of licorice, is often used as an anti-inflammatory, antimicrobial, anti-diabetic, and anti-tussive agent [5, 8]. Moreover, isoliquiritigenin has been found to inhibit growth and aromatase activity of breast cancer cells and thus, has potential to be used as a chemotherapeutic agent in breast cancer [911].…”
Section: Introductionmentioning
confidence: 99%
“…There is a global attempt to design more powerful drugs for the treatment of lung cancer with low toxicity, but the results are unsatisfactory. Fortunately, emerging evidence has demonstrated that some herbal drugs, such as the active components of licorice, could be better choices to improve the current therapeutic strategy [2][3][4].…”
Section: Introductionmentioning
confidence: 99%